2015
DOI: 10.1155/2015/607692
|View full text |Cite
|
Sign up to set email alerts
|

Mmu-miR-27a-5p-Dependent Upregulation of MCPIP1 Inhibits the Inflammatory Response in LPS-Induced RAW264.7 Macrophage Cells

Abstract: Lipopolysaccharide (LPS) stimulates macrophages to release proinflammatory cytokines. MicroRNAs (miRNAs) are short noncoding RNAs that are involved in inflammatory reaction. Our previously study identified the downregulated expression of mmu-miR-27a-5p in RAW267.4 cells treated with LPS. To dissect the mechanism that mmu-miR-27a-5p regulates target genes and affects proinflammatory cytokine secretion more clearly, based on previous bioinformatics prediction data, one of the potential target genes, MCPIP1 was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In macrophages, miR-27a overexpression enhanced the expression of proinflammatory cytokines (IL-1β, IL-6, IL-12, and TNF-α), and diminished the expression of anti-inflammatory cytokine IL-10 ( 17 ). Also in macrophages, mmu-miR-27a was indicated as a proinflammatory gene, as its target gene MCPIP1 could decrease the secretion of IL-6, IL-1β, and IL-10, which were stimulated by LPS ( 15 ). These data indicated the complex and critical roles of miR-27a in inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…In macrophages, miR-27a overexpression enhanced the expression of proinflammatory cytokines (IL-1β, IL-6, IL-12, and TNF-α), and diminished the expression of anti-inflammatory cytokine IL-10 ( 17 ). Also in macrophages, mmu-miR-27a was indicated as a proinflammatory gene, as its target gene MCPIP1 could decrease the secretion of IL-6, IL-1β, and IL-10, which were stimulated by LPS ( 15 ). These data indicated the complex and critical roles of miR-27a in inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…57 Influenza A virus (IAV) hijacks the miR-9/Regnase-1 axis, thereby benefitting the viral life cycle. 58 It has been reported that miR-139 and miR-27a-5P promote IL-6 expression by targeting Regnase-1 in human OA chondrocytes 59,60 (Figure 1b). In contrast, Regnase-1 acts as a broad suppressor of miRNA synthesis by counteracting Dicer, a central ribonuclease in miRNA processing.…”
Section: Functional Termination Of Regnase-1 Through Multiple Mechanismsmentioning
confidence: 97%
“…Among them, we observed that miR-27a was one of the most dysregulated miRNAs, which has been shown to have a protective effect in many injury models [22][23][24]. Furthermore, miR-27a has been demonstrated to play an important role in regulating inflammatory response [24][25][26]. However, whether miR-27a plays a similar role in ALI remains unknown.…”
Section: Mir-27a Was Downregulated In Lps-induced Acute Lung Injury Imentioning
confidence: 99%